2015
DOI: 10.1093/ejcts/ezv221
|View full text |Cite
|
Sign up to set email alerts
|

Does postoperative blood pressure influence development of aortic regurgitation following continuous-flow left ventricular assist device implantation?

Abstract: BP readings at 3 months and 6 months showed a statistically significant association with ≥mild AR following CF-LVAD implantation, with systolic blood pressure at 3 months, aortic valve closure and longer support duration being independent predictors. Clinical implications of these data may warrant consideration of aggressive early control of BP to protect against the development/progress of AR following CF-LVAD implantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 19 publications
0
22
0
1
Order By: Relevance
“…In three of the eight studies, significant AR was defined as being more than mild [4,6,11]. In five of the included studies, patients were considered to have significant AR if it was mild or greater [7,10,[12][13][14]. The incidence after cf-LVAD implantation according to the AR grading criteria was 37% (203 of 548).…”
Section: Definition and Incidence Of Significant Aortic Regurgitationmentioning
confidence: 99%
See 3 more Smart Citations
“…In three of the eight studies, significant AR was defined as being more than mild [4,6,11]. In five of the included studies, patients were considered to have significant AR if it was mild or greater [7,10,[12][13][14]. The incidence after cf-LVAD implantation according to the AR grading criteria was 37% (203 of 548).…”
Section: Definition and Incidence Of Significant Aortic Regurgitationmentioning
confidence: 99%
“…Six studies provided data on the left ventricular ejection fraction [4,6,[10][11][12][13], and five reported left ventricular end-systolic diameters [7,10,11,13,14]. Six studies published the observed left ventricular end-diastolic diameters [6,7,10,11,13,14]. Briefly, the pooled functional and structural left ventricular data did not show a significant difference between the investigated and control cohorts (left ventricular ejection fraction MD À1.…”
Section: Left Ventricular Function and Dimensionsmentioning
confidence: 99%
See 2 more Smart Citations
“…More recent studies have identified lower blood pressure as protective from the development of aortic insufficiency (19). Additionally, strict blood pressure control is increasingly recognized as a therapeutic goal to reduce the rates of hemorrhagic and embolic stroke (20,21).…”
mentioning
confidence: 99%